Intersections of financial literacy, citizenship, and spirituality : examining a forbidden frontier of social education - Lucey, Thomas A. (Emerald points., 2019)
Conversations about social education curricula largely neglect elements of spirituality and consciousness. This omission undermines the quality of the learning that occurs. This book presents spirituality as a legitimate basis for reframing these social decision-making by examining how revisiting notions of spirituality may redefine patterns of social relationships and financial choices. This work presents an interpretation of spirituality that offers the foundation for an alternative ideology to capitalist practices founded on principles of merit and blame. By acknowledging a spiritual sense of being, citizens may gain a renewed sense of personal responsibility toward community and social justice. The work draws from a fate-based ideology, which claims that individual and group choices originate from conditions outside their control. It describes art-based instructional processes that may stimulate students' affective awareness. It encourages facilitation of compassionate environments founded on principles of selflessness and provides a basis for conversation about the nature of social education and its foundations. This book represents an invaluable resource for researchers, leaders and practitioners in the field of social education.